Diversity of birds captured by mist-netting in the understorey of Gunung Gading National Park, Sarawak, Borneo - Nur Azirah Arif; J Mohd-Azlan (KUKILA, 2014)
The diversity of understorey birds at Gunung Gading National Park was examined from November 2011 to April 2012 using mist nets with total effort of 177 nets days, revealed 114 individuals representing 13 families and 38 species. Including previous studies, a total of 62 bird species have been netted in Gunung Gading National Park. The most diverse families were Pycnonotidae and Timaliidae, both with 9 species captured, followed by Muscicapidae represented by 4 species. The bird diversity (H’= 3.18) was higher than that reported in previous studies. Cumulative results suggest that previous netting studies has been insufficient to reveal the total understorey bird diversity and the number of species netted and added shows little sign of tailing off suggests that additional effort is required.